Nasal valve obstruction: a comprehensive analysis of the current literature and proposal of a management algorithm - Francesca Pirola; Raymond Kim; Richard Douglas (Frontiers in Surgery)
Nasal valve obstruction (NVO) remains challenging to diagnose and treat. This review explores the persisting controversies of NVO management, emphasising the lack of consensus in diagnostic criteria and treatment protocols among otolaryngologists and facial plastic surgeons. Recent surveys highlight the central dilemma: for many patients who have both septal deviation and NVO, a septoplasty alone provides adequate symptomatic improvement. However, some with this combination of problems continue to be troubled by nasal obstruction if only a septoplasty is performed. This underscores the critical question of when NVO necessitates specific surgical intervention. The varying diagnostic approaches that have been used and the limited outcome data currently available conspire to make this question difficult to answer with certainty. This review will also address the role of the inferior turbinates in NVO management, proposing their inclusion in NVO surgical planning. Other techniques will also be discussed for their potential impact on nasal valve dynamics. Both endonasal and open approaches to correcting the caudal septum need to be considered when discussing NVO repair. A treatment algorithm for NVO will be presented as a practical guide for the management of this condition.